Persistent deficiency of mucosal-associated invariant T cells during dermatomyositis. (17th December 2019) - Cassius, Charles; Branchtein, Mylene; Battistella, Maxime; Amode, Reyhan; Lepelletier, Clémence; Jachiet, Marie; de Masson, Adèle; Frumholtz, Laure; Chasset, François; Amoura, Zahir; Mathian, Alexis; Samri, Assia; et al.
Abstract: Objectives: Mucosal-associated invariant T (MAIT) cells are innate-like lymphocytes that are important for antibacterial immunity and may have regulatory roles. MAIT cells are decreased during SLE. However, their frequencies and phenotype have not been investigated in DM. We studied MAIT cell frequencies and phenotype in DM patients with active and inactive disease (after treatment). Methods: Peripheral blood flow cytometry analysis of MAIT cells was compared between DM ( n = 22), SLE ( n = 10), psoriasis ( n = 7) and atopic dermatitis ( n = 5) patients, and healthy controls ( n = 19). Results: A dramatic decrease of circulating MAIT cell frequency was observed in active DM and SLE patients compared with healthy controls and other inflammatory skin diseases [active DM: median = 0.25% (interquartile range 0.19–0.6%), P < 0.0001; active SLE: median = 0.61 (0.55–0.77), P < 0.0001 vs healthy controls: 2.32% (1.18–4.45%)]. MAIT cells from active DM patients had an abnormal phenotype including increased expression of CD25 and cytotoxic T-lymphocyte-associated protein 4 that correlated with their low frequency in the blood. Conclusion: In DM, peripheral blood MAIT cells are dramatically reduced and have an activated/exhausted phenotype that may be linked to increased activation-induced cell death.